Sign System Gedung Kearsipan dan Perpustakaan Sumatera Barat - M. Farid Mediatama; Aditya Hanum Widharsa (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The Archives and Library Office of West Sumatra Province is a government institution that serves as a center for archive management and public literacy services. This building is visited by various groups, including agency staff, students, university students, and the general public. However, based on preliminary observations, several issues were identified regarding the existing signage system in the building, which was found to be inadequate, lacking in informativeness, and in many cases, unfit for use—making it difficult for visitors to navigate the space. This study aims to design a more effective and communicative signage system using a visual communication design approach. Data collection methods included direct observation and SWOT analysis to identify the strengths, weaknesses, opportunities, and threats of the current signage conditions. The design process employed the Design Thinking method, consisting of five stages: empathize, define, ideate, prototype, and test. The outcome of this process includes five primary media: pictograms, floor plan boards, ground floor information boards, directional signs, and room information signs. Additionally, five supporting media were designed: staff ID cards, lanyards, library membership cards, folder maps, and bookmarks. The developed designs were evaluated through validation and feasibility testing involving two design experts and three visitors as respondents. Based on the assessment results, the design was rated as excellent, with an average score of 4.95 from the experts, and all general respondents gave positive feedback regarding the visual aspects, legibility, and informational function of the designed signage system.